METHODS FOR THE ARRANGEMENT OF IMMERSED TUBE TUNNELS DURING CONSTRUCTION BASED ON STRUCTURALLY UNSTABLE SOILS - E. N. Kurbatskiy; N. V. Kupchikova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of the research is to develop the most effective construction and technological methods for strengthening the bottom of rivers and bays, composed of weak structurally unstable soils, including zones with seismic activity, using pile foundations with broadening and rock filling with micropiles.Methods. The method of constructing combined transport transitions was applied, consisting of overpasses running over relatively shallow channels from coasts to artificial islands on which the route enters tunnels crossing deep shipping canals.Results. The foreign experience in the construction of immersed tube tunnels in the construction of transport crossings through the extended river and sea barriers has been analytically generalised. The features, advantages and disadvantages of the construction of immersed tube tunnels in some countries of the world are revealed.Conclusion. A large number of already constructed and operated transport transits, including immersed tube tunnels, testifies to the advantages of such projects, as compared to other types of transport transitions like bridges and tunnels constructed using mining techniques. Constructiontechnological methods for strengthening the bottom of rivers and bays, composed of weak structurally unstable soils, are proposed. When selecting a design of a bridge to ensure the passage of hightonnage vessels, it is necessary to build large-span bridges on high supports. Weak, structurally unstable soils, deep bedding of bedrock and high seismicity of the area will create serious problems in the construction and operation of such structures. The natural vibration frequencies of the large-span bridges fall into the region of the dominant earthquake frequencies, which can lead to resonant phenomena and damage the structure even under weak seismic influences. Tunnels are less susceptible to seismic impacts, since, unlike ground structures, they don't experience resonance phenomena. When seismic waves pass, the tunnels are deformed in the same way as the surrounding soil massif (if the soil is solid), or much less (if the soil is weak). Deformations are usually small and do not pose a serious danger for tunnel lining. Structural and technological solutions for long transit routes through straits composed of weak soils along the bottom in the territories of disarticulated landscapes can be the most economical, reliable and acceptable when choosing the intersection by transport routes from the point of view of costs, time of construction and use of modern technologies.